2004
DOI: 10.1213/01.ane.0000134808.52676.4d
|View full text |Cite
|
Sign up to set email alerts
|

Neurological Monitoring for Congenital Heart Surgery

Abstract: The incidence of neurological complications after pediatric cardiac surgery ranges from 2% to 25%. The causes are multifactorial and include preoperative brain malformations, perioperative hypoxemia and low cardiac output states, sequelae of cardiopulmonary bypass, and deep hypothermic circulatory arrest. Neurological monitoring devices are readily available and the anesthesiologist can now monitor the brain during pediatric cardiac surgery. In this review we discuss near-infrared cerebral oximetry, transcrani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
109
0
16

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(125 citation statements)
references
References 60 publications
0
109
0
16
Order By: Relevance
“…During circulatory arrest, cerebral oximetry SctO 2 will decrease as oxygen is being metabolized by brain tissue (our unpublished observations). 8,9 SctO 2 is much more sensitive to brain oxygenation compared to pulse oximetry. For neonates, pulse oximetry SpO 2 readings typically vary from 85 to 100%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During circulatory arrest, cerebral oximetry SctO 2 will decrease as oxygen is being metabolized by brain tissue (our unpublished observations). 8,9 SctO 2 is much more sensitive to brain oxygenation compared to pulse oximetry. For neonates, pulse oximetry SpO 2 readings typically vary from 85 to 100%.…”
Section: Discussionmentioning
confidence: 99%
“…Many research and observational studies were performed with neonates using various types of NIRS/cerebral oximetry monitors. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] However, no food and drug administration (FDA) approved cerebral oximeter is available for neonates. Successful validation of cerebral oximetry for the FDA has been done in human adult volunteer studies under protocols were jugular bulb and arterial blood samples were obtained under different levels of fractional inspired oxygen (FiO 2 ) levels.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Recent studies have also examined the use of NIRS to measure the saturation of other tissues, including the intraperitoneal monitoring of pH in the small bowel, transcutaneous monitoring of lower abdominal perfusion indexed to cerebral perfusion in neonates with acute abdomen and transcutaneous monitoring of renal blood flow in neonates undergoing Norwood palliation. [8][9][10][11] This is the first report of monitoring post-ductal regional saturations with NIRS during surgical PDA ligation.…”
Section: Introductionmentioning
confidence: 99%
“…Cerebral oximetry does not need pulsatile flow to determine SctO 2 ; therefore, cerebral oximetry can be used reliably during nonpulsatile flow situations, such as cardiopulmonary bypass, deep hypothermia circulatory arrest, high blood loss/shock, CPR and regional lowflow cerebral perfusion. 5,6,[17][18][19] Our results show that SctO 2 events occur more frequently before starting ECMO compared to after the onset of ECMO. Although ECMO has its known potential risks, we observed that cerebral oxygenation increases during ECMO, and the frequency of SctO 2 events dramatically decreases (assuming normal ECMO pump operation).…”
Section: Discussionmentioning
confidence: 56%